Effect of nitrogen and phosphorus sources on amylase production in seed born fungi of maize - Kulkarni, Anil U; Chavan, Ashok M; Kesare, Umesh T; Pawar, Sanjay M (Current Botany, 2012)
Starch degrading amylolytic enzymes are of great significance in biotechnological application ranging from food, fermentation, and textile to paper industries. Amylase enzyme action of ten dominating fungi viz. Alternaria alternata, Aspergillus flavus, A niger, A terrus, Curvularia lunata, Fusarium oxysporum, Helminthosporium tetramera, Penicillium notatum, Rhizoctonia solani & Trichoderma viride isolated from different varieties of maize seeds were studies under the influences of nitrogen & phosphorus sources. The results are very helpful to minimize the bio-deterioration of maize seeds in different storage condition.